Echinoderms Diversity in Cibuaya Beach Ujung Genteng, West Java - Triacha, Zarfa Izra Egharitya Chipta; Pertiwi, Meilisha Putri; Rostikawati, Teti (Jurnal ILMU DASAR, 2021)
The research about Echinoderms diversity in Cibuaya Beach Ujung Genteng, West Java has been conducted from February to July 2019. It aimed to know diversity index of Echinoderms. It used belt transect method with three stations in the intertidal zone. Sampling technique used purposive sampling. The observation data are included primary data (the number of phylum Echinoderm’s species in the transect) and environmental data (pH, salinity, temperature, depth, current strength, and substrate). The population in this study was all species of Echinoderms found in the intertidal zone. The sample in this study was the species of Echinoderms found in the area of the station. Based on the result, the study obtained 8 species of Echinoderms, consisted of 3 classesand classified into 5 orders, 5 families, and 6 genera. The diversity index is classified as low with the average value of 0.62. The evenness index is classified as low with the average value of 0.37. The dominance index is classified as moderate with the average value of 0.67. Keywords: diversity, echinoderms, cibuaya beach, Ophiuroidea, Echinoidea, Holothuroidea.